1997
DOI: 10.1136/fn.76.1.f31
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance and implications of antenatal hydronephrosis

Abstract: Detailed antenatal sonography was performed on 18 766 pregnant women between 1990 and 1994. Antenatal hydronephrosis, defined as an antero-posterior diameter of the renal pelvis (APPD) greater than 5 mm, was detected in 100 cases (0.59%). Sixty four infants had postnatal hydronephrosis at one and/or six weeks after delivery; 21 of these had urological anomalies.Twelve infants had vesico-ureteric reflux. In all refluxing units the APPD of the renal pelvis was less than 10 mm. Three patients had obstruction at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
3
8

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(113 citation statements)
references
References 31 publications
5
97
3
8
Order By: Relevance
“…Most studies measured fetal RP size at approximately 20 wk of gestation, corresponding to the timing of routine second trimester anomaly scan. The earliest reported fetal ultrasound was at 14 wk of gestation (21). Most studies reported that postnatal scans were not performed within 2 d after birth (17,20,22,23,(27)(28)(29)(30)(31), which may be important because newborns are initially oliguric and false-negative results are common at this time: 4 studies did not specify the earliest age at postnatal ultrasound assessment (18,29,30,33).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies measured fetal RP size at approximately 20 wk of gestation, corresponding to the timing of routine second trimester anomaly scan. The earliest reported fetal ultrasound was at 14 wk of gestation (21). Most studies reported that postnatal scans were not performed within 2 d after birth (17,20,22,23,(27)(28)(29)(30)(31), which may be important because newborns are initially oliguric and false-negative results are common at this time: 4 studies did not specify the earliest age at postnatal ultrasound assessment (18,29,30,33).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Five hundred and six potentially relevant studies were identified, of which 18 met the inclusion criteria (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Two studies reported overlapping patient cohorts but different outcomes (27,28).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigators, however, have not mentioned any loss of patients in their ANH programs. [4][5]7,10,14,[19][20] In one-fourth of cases, our MFM specialists recommended follow-up after birth with their pediatrician. As suggested by our data, half of these infants were deemed to be healthy and no postnatal renal US or other consultations were done.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Moreover, congenital obstructive nephropathy, frequently accompanied by hydronephrosis, is a common cause of renal failure in children. 3 In turn, hydronephrosis is frequently associated with effacement of the renal medulla, the inner zone of the kidney.…”
Section: Introductionmentioning
confidence: 99%